Exacerbation of myopathy in glycogen debrancher deficiency after liver transplantation: case report and review of the literature - Rauber, Conrad; Pfeiffenberger, Jan; Mehrabi, Arianeb; Mieth, Markus; Zizer, Eugen; Merle, Uta (Transplantation proceedings, 2024)
Background - Glycogen storage disorder (GSD) type IIIa is a rare inherited genetic disorder affecting liver and muscle tissue. Liver transplantation (LT) improves metabolic control, but muscle involvement persists. - Case - We report the case of a 31-year-old man who underwent orthotopic LT for end-stage liver disease caused by GSD type IIIa. After LT, he developed worsening clinical signs of myopathy, along with exponentially increasing levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) and creatine kinase. Liver-related elevations of AST and ALT were excluded through liver biopsy and endoscopic cholangiography; consequently, AST and ALT elevations were attributed to the underlying muscle involvement. Exacerbation of muscle disease after LT could be attributed to restoration of liver glycogen metabolism after LT, leading to increased glucose accumulation in muscle cells, where the gene defect persists. A dietary intervention with a high-protein, ketogenic diet was initiated but did not lead to significant improvement of myalgia. - Conclusion - LT exacerbated muscle disease in a patient with GSD type IIIa. Patients should be counseled about this possible side effect of LT in GSD type IIIa.
Gesehen am 03.02.2025